Dampak Globalisasi Terhadap Dinamika Budaya Dalam Konteks Komunikasi Bisnis - Ayu Lestari Sitio; Cai Siregar; Dinda Karunia Putri; Suhairi Suhairi (Universitas Dian Nuswantoro, 2022)
This article discusses the impact of globalization on cultural dynamics in the context of business communication. Globalization has changed the business landscape with intense cultural exchanges thereby increasing interactions between countries. In the context of business communication, complex cultural dynamics can influence the way individuals and organizations communicate, interact, and build effective business relationships.The writing of this article uses the literature or literature study method, in which the authors reveal that globalization has brought many significant changes in business and cultural communication. In the context of global business communication, the important aspects are the growth of multiculturalism, the adoption of global languages, and the influence of culture in marketing. In dealing with the dynamics of diverse cultures it is also very important to have a good cultural understanding, adopt communication styles, and use effective strategies.